2015
DOI: 10.1093/mnras/stv2687
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of accretion discs around a kerr black hole using extended magnetohydrodynamics

Abstract: Black holes accreting well below the Eddington rate are believed to have geometrically thick, optically thin, rotationally supported accretion discs in which the Coulomb mean free path is large compared to GM/c 2 . In such an environment, the disc evolution may differ significantly from ideal magnetohydrodynamic predictions. We present non-ideal global axisymmetric simulations of geometrically thick discs around a rotating black hole. The simulations are carried out using a new code grim, which evolves a covar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 41 publications
(59 reference statements)
4
65
0
1
Order By: Relevance
“…This is because the field lines in our simulation are primarily toroidal while the temperature gradients are primarily poloidal. Foucart et al (2016) came to a similar conclusion for the effect of ion conduction on the fluid dynamics when including it in the total fluid stress-energy tensor. The small effect of electron conduction in our model suggests that future modelling of electron thermodynamics can probably neglect electron conduction, greatly simplifying the numerics and reducing the computational expense by a factor of ∼ 4.…”
Section: Discussionsupporting
confidence: 55%
“…This is because the field lines in our simulation are primarily toroidal while the temperature gradients are primarily poloidal. Foucart et al (2016) came to a similar conclusion for the effect of ion conduction on the fluid dynamics when including it in the total fluid stress-energy tensor. The small effect of electron conduction in our model suggests that future modelling of electron thermodynamics can probably neglect electron conduction, greatly simplifying the numerics and reducing the computational expense by a factor of ∼ 4.…”
Section: Discussionsupporting
confidence: 55%
“…We ignore, however, anisotropic heat conduction along magnetic field lines. The effect of this mechanism on optically thin accretion flows has recently been studied by Ressler et al (2015), Chandra et al (2015), and Foucart et al (2016). Ressler et al (2015), in particular, have shown that the anisotropic heat conduction contributes to at most 20% of the isotropic heat flux.…”
Section: Implemented and Not Implemented Physicsmentioning
confidence: 99%
“…This ratio is a free parameter that is poorly constrained both by theory and observations. We choose values consistent with the findings of recent, sophisticated models of the electron thermodynamics in collisionless accretion flows (Ressler et al 2015;Foucart et al 2016;Saḑowski et al 2017), which show that the electron temperature is comparable to the proton temperature in highly magnetized regions of the flow. Modeling the electron physics in accretion disks and jets remains an active area of research, which will hopefully be informed further by upcoming observations with the EHT.…”
Section: Summary and Discussionmentioning
confidence: 99%